English syllabus proposal for teaching english as a foreign language in the San Jerónimo and Antisana Private Kindergarten, Píntag - Matute Anagumbla, Víctor Hugo (2005)
Since there have been schools, there has been the need to improve teaching. Thousands of people have spent time, energy and money in order to make decisions about how to do our language education more efficient. Over the past few years, two private schools have been created in Píntag. These schools claim to offer a more effective language education inside the town. However, the experience shows that at the end of the elementary school, children from these kindergartens cannot even use the foreign language in informal situations. Many reasons to explain this failure could be mentioned; however, that is not the purpose of this paper. The purpose of this work is to propose a kindergarten English syllabus for the teaching of English as a foreign language. This syllabus might be used as a guide for kindergarten teachers of English as a foreign language in the San Jerónimo and Antisana private schools in Píntag. The kindergarten level has been chosen because this is the first step in formal education for most children. Children at the kindergarten age are expected to learn a lot of abilities, skills and psychomotor activities. But mainly, they are expected to acquire and develop useful verbal competence, as well as the ability to produce and use this verbal competence during their whole life. On the other hand, these abilities will facilitate the learning process in the coming years. Therefore, greater emphasis should be given to language programs for children especially for foreign languages. Together with these abilities, the development of the speech in the native language will help to internalize the foreign language skills.